Analysis of the main antioxidant enzymes in the roots of Tamarix ramosissima under NaCl stress by applying exogenous potassium (K+) - Chen, Yahui; Li, Haijia; Zhang, Shiyang; Du, Shanfeng; Zhang, Jinchi; Song, Zhizhong; Jiang, Jiang (Frontiers in Plant Science, 2023)
Introduction Salinization affects more than 25% of the world's arable land, and Tamarix ramosissima Ledeb (T. ramosissima), the representative of Tamarix plants, is widely grown in salinized soil. In contrast, less is known about the mechanism of potassium's antioxidative enzyme activity in preventing NaCl stress damage to plants. Method This study examined changes in root growth for T. ramosissima at 0h, 48h, and 168h, performed antioxidant enzyme activity assays, transcriptome sequencing, and non-targeted metabolite analysis to understand changes in their roots as well as changes in the activities of superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT). Quantitative real-time PCR (qRT-PCR) was used to identify differentially expressed genes (DEGs) and differential metabolites associated with antioxidant enzyme activities. Result As the time increased, the results showed that compared with the 200 Mm NaCl group, the root growth of the 200 mM NaCl + 10 mM KCl group increased, the activities of SOD, POD and CAT increased the most, but the contents of hydrogen peroxide (H2O2) and Malondialdehyde (MDA) increased less. Meanwhile, 58 DEGs related to SOD, POD and CAT activities were changed during the application of exogenous K+ for 48h and 168h in T. ramosissima. Based on association analysis of transcriptomic and metabolomic data, we found coniferyl alcohol, which can act as a substrate to label catalytic POD. It is worth noting that Unigene0013825 and Unigene0014843, as POD-related genes, have positively regulated the downstream of coniferyl alcohol, and they have a significant correlation with coniferyl alcohol. Discussion In summary, 48h and 168h of exogenous K+ applied to the roots of T. ramosissima under NaCl stress can resist NaCl stress by scavenging the reactive oxygen species (ROS) generated by high salt stress by enhancing the mechanism of antioxidant enzyme activity, relieving NaCl toxicity and maintaining growth. This study provides genetic resources and a scientific theoretical basis for further breeding of salt-tolerant Tamarix plants and the molecular mechanism of K+ alleviating NaCl toxicity.